(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
With the reform of the legal system for combating drugs in 2006, Law 11.343/2006 repealed the old Law 6.368/1976, making a number of relevant changes, including that relating to the minimum limit of the custodial sentence for the crime of trafficking, from three to five years’ imprisonment, revealing, prima facie, greater rigor on the part of the legislator.In line with the above, it can be concluded that: - the interpretation of §4 of article 33 of the Drug Law ignoring Law no. 12. the interpretation of §4 of article 33 of the Drugs Law ignoring Law No. 12.850/2013 is unacceptable, under penalty of incongruity in the legal-penal system, which is why the new law requires a re-examination of the understatement discussed; - the hitherto open concept of “integrating a criminal organization” now has precise contours, in addition to constituting its own criminal type, which is expressed in articles 1, §1, and 2, of the new law; - these outlines must be taken into account when examining the cause of reduction for drug trafficking, so that it is only removed because the defendant is a member of a criminal organization if he or she has a stable and permanent link to an organized structure made up of four or more people; - Furthermore, since this circumstance is now an autonomous crime, its characterization depends on full proof, since it is no longer a circumstance that modifies the punitive claim, but an element of the criminal type, highlighting the incoherence of saying that the same fact characterizes “being part of a criminal organization” for the purposes of the Drug Law but not for those of the Criminal Organization Law, which make up the same legal-penal system; - Nevertheless, the interpretation according to which the diminishing factor does not apply in the case of dedication to criminal activities, which can be proven by evidence, is still valid.